2020
DOI: 10.1177/2325967120945322
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications After Primary Arthroscopic Suprapectoral Versus Open Subpectoral Biceps Tenodesis for Superior Labral Anterior-Posterior Tears or Biceps Abnormalities: A Systematic Review and Meta-analysis

Abstract: Background: Biceps tenodesis is a surgical treatment for both superior labral anterior-posterior (SLAP) tears and long head of the biceps tendon (LHBT) abnormalities. Biceps tenodesis can be performed either above or below the pectoralis major tendon with arthroscopic or open techniques. Purpose: To analyze the outcomes and complications comparing primary arthroscopic suprapectoral versus open subpectoral biceps tenodesis for either SLAP tears or LHBT disorders. Study Design: Systematic review; Level of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 69 publications
(145 reference statements)
0
27
1
Order By: Relevance
“…42 Other investigators have reported much lower incidences of persistent cosmetic deformity after arthroscopic tenodesis (<5%), with some reporting no instances of cosmetic deformity postoperatively. 12,43,46 Although the average biceps apex distance between the operative and nonoperative sides did not differ in our analysis, a noticeable Popeye deformity developed postoperatively in 5 patients SHORT-TERM ARTHROSCOPIC TENODESIS e7 (10.0%). These findings are clinically significant considering that many authors advocate the performance of tenodesis versus tenotomy in active or working populations, such as our population, owing to the decreased reported risk of cosmetic deformity.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…42 Other investigators have reported much lower incidences of persistent cosmetic deformity after arthroscopic tenodesis (<5%), with some reporting no instances of cosmetic deformity postoperatively. 12,43,46 Although the average biceps apex distance between the operative and nonoperative sides did not differ in our analysis, a noticeable Popeye deformity developed postoperatively in 5 patients SHORT-TERM ARTHROSCOPIC TENODESIS e7 (10.0%). These findings are clinically significant considering that many authors advocate the performance of tenodesis versus tenotomy in active or working populations, such as our population, owing to the decreased reported risk of cosmetic deformity.…”
Section: Discussionmentioning
confidence: 66%
“…These findings may suggest that patients experiencing postoperative cosmetic deformity may also perceive some functional deficit. However, these findings should be interpreted with caution because this comparison is likely underpowered given the small sample size of failures and insufficient to draw 46,53,54 Perhaps other options for suture anchor fixationdor the use of additional anchors to fortify the repairdmay lead to improved tenodesis fixation and decreased rates of deformity. In addition, an onlay technique may result in decreased tendonbone healing in comparison to tunnel-based techniques, contributing to failure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that arthroscopic suprapectoral versus open subpectoral tenodesis techniques have unique complications. 76 This text will focus primarily on open subpectoral tenodesis complications. In a 2020 systematic review and meta-analysis by Deng et al, it was noted that patients had residual pain in 4.7% of cases after open tenodesis.…”
Section: Managementmentioning
confidence: 99%
“…Two of the 295 (0.7%) open cases were reported to have nerve-related injuries, though one was determined to be due to an interscalene block perioperatively. 76 Surgeons should pay close attention to sterile technique and be gentle with traction during tenodesis procedures, as branches of the brachial plexus, particularly the musculocutaneous nerve, may traverse near the tenodesis site. Neurovascular complications and infection risk are the most commonly cited reasons for an arthroscopic approach to the BT, however, the senior author has performed over 500 BT procedures using the technique described above with no neurovascular complications or need to return to the operating room for irrigation and debridement.…”
Section: Managementmentioning
confidence: 99%